Study of Mass-loss in the Planetary Nebula NGC 1514 - Aryal, B; Mishra, A; Weinberger, R (Scientific World, 2010)
The planetary nebula NGC 1514 is found to reside within giant dust structures which may represent fossil records of its progenitor's transition from spherically symmetric to bipolar mass loss. The transition from spherically symmetric Asymptotic Giant Branch (AGB) mass loss to aspherical Planetary Nebulae (PNe) is an intriguing problem of stellar astrophysics. On 12 μm maps of the Infrared Astronomical Satellite (IRAS) we detected a huge (2.6pc) roundish emission nebula around the evolved PN NGC 1514. On 100 and 60 μm IRAS maps we additionally found two giant (1-2 pc) bipolar dust emission structures centered on NGC 1514. The total mass of all these structures is 2.2 ± 1.4 solar mases. We argue that NGC 1514 and its dusty surroundings represent the preserved history of the main mass loss phases of a star of intermediate initial mass. Key words: Interstellar medium; Infrared astronomy; Planetary nebula; Stars; Asymptotic giant branch DOI: 10.3126/sw.v5i5.2647 Scientific World, Vol. 5, No. 5, July 2007 6-9